A comparative evaluation of the psychophysiological state of trainers - Galiullina, S.D.; Kogan, O.S.; Gerasimova, D.I.; Safina, E.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the psychophysiological qualities of coaches who have not previously participated in high-performance sport and of high-class athletes who have moved to coaching work after the completion of their career in high-performance sport, in terms of the level of their stress resistance, self-control, motivation, anxiety and performance in their subsequent professional activity. Methods and structure of the study. An analysis of the features of the professional activity of coach-instructors was carried out on the basis of the results of our own studies and data from the scientific literature. In coaches of both groups, psychophysiological indicators were studied that characterise their state of adaptation to loads, using the following methods: Lüscher, Cattell, the Ehlers questionnaire, the proofreading test, the tapping test and the simple visual-motor reaction (SVMR). Levels of their anxiety, tension, conflict and other indicators were studied. Results and conclusions. The study of psychophysiological indicators reflecting the state of adaptation of the body to physical and mental loads in coaches holding high sporting titles and amateur coaches who had not previously participated in high-performance sport, indicated a reliably higher level of anxiety and a certain decrease in physical performance in coaches of the main group compared with the control. Since the level of adaptation of the body of those engaged in high-performance sport to increased loads is not unlimited, this gives rise to the necessity for strict medical monitoring of their health, both in their participation in sport and on transition to coaching and instructional activity.